Room temperature observation of the correlation between atomic and electronic structure of graphene on Cu(110). Issue 100 (14th October 2016) - Chagas, Thais; Cunha, Thiago H. R.; Matos, Matheus J. S.; dos Reis, Diogo D.; Araujo, Karolline A. S.; Malachias, Angelo; Mazzoni, Mario S. C.; Ferlauto, Andre S.; Magalhaes-Paniago, Rogerio
Abstract : We have used atomically-resolved scanning tunneling microscopy and spectroscopy to study the interplay between the atomic and electronic structure of graphene formed on copper via chemical vapor deposition. Abstract : In this work we have used atomically-resolved scanning tunneling microscopy and spectroscopy to study the interplay between the atomic and electronic structure of graphene formed on copper via chemical vapor deposition. Scanning tunneling microscopy directly revealed the epitaxial match between a single layer of graphene and the underlying copper substrate in different crystallographic orientations. Using scanning tunneling spectroscopy we have directly measured the electronic density of states of graphene layers near the Fermi level, observing the appearance of a series of peaks in specific cases. These features were analyzed in terms of substrate-induced perturbations in the structural and electronic properties of graphene by means of atomistic models supported by density functional theory calculations.